Seven or less Fractions is Not the Standard of Care for Intermediate-Risk Prostate Cancer. Issue 3 (March 2020) - Tree, A.C.; Dearnaley, D.P.
Abstract: Evidence is accumulating for seven and less fractions in localised prostate cancer, including one large randomised trial. However, there is much more evidence yet to come and changing practice in advance of this may be premature. We review the reasons to persist with moderate hypofractionation for prostate cancer radiotherapy, until the results of further phase III studies are known.